Using Text Mining to Explore Acceptance of Zero-Touch Fintech Service Innovation: Internet Word-of-Mouth of R Digital Bank - Shu-Chin Huang; Ching-Mei Zhu; Maw-Liann Shyu (Engineering Proceedings, 2023)
By using the texts of Internet word-of-mouth, the most popular digital banking services and its users’ perceptions of the usefulness and ease of use of these services were explored. Python was used to capture 2026 valid texts on the Industrial Square Banking Service Edition, covering the period of 2016−2020. The results show that (1) the digital banking Fintech provided digital and traditional services, (2) positive comments were seen more than negative comments for confirmation and perceived usefulness while negative comments were more than positive comments for satisfaction and continuance intention, and (3) satisfaction via Internet word-of-mouth was seen the most frequently.